Strukturisasi Norma: Pengarusutamaan Gagasan Neoliberal dalam Pembangunan di Negara Pasca-Kolonial (Pengalaman Amerika Latin dan Asia) - Wirasenjaya, Ade Marup (Jurnal Ilmu Sosial dan Ilmu Politik, 2012)
Neoliberalism has create structurization process in post collonial states. The structurization is not only affecting the state souvereignty, but also shape norms and identity. By using the constructivistâs view of the "steering", this paper tries to elaborate patterns of disciplinary regime imposed by international development institutions toward post-colonial states. This paper assured that the post-colonial ties is not the attribution, but rather a construction that has a long process of the integration process in the previous phase of capitalism.